Remodelagem de uma usina sucroalcooleira para incremento da cogeração de energia com aproveitamento do palhiço - Lacerda, Kaito Arnoni [UNESP] (2015)
Due to the current environmental policies applied to the sugar and ethanol industry, which propose the prohibition of the canebrake burning act, tons of biomass in the form of sugarcane trash are being left on the field. Thus, in a reality of potential energy crisis in the country and pursuit of sustainable alternatives on the energy generation, the bioenergy suits as an important solution for this market and, therefore, the energy potential of the sugarcane trash comes to be investigated as an additional source at the power cogeneration plants. In this context, this work proposes a study for the viability of solutions which aim a more useful end to the sugarcane trash in an established and operating sugarcane mill in São Paulo state, generating, then, greater electricity surpluses in both harvest and interharvest seasons. In order to provide evidences for the viability of each solution, thermodynamic, thermoeconomic and economic inquiries were applied. Five adjustment proposals of the cogeneration plant were analyzed, wherein, four of them were modified and improved in the already established plant, whilst for the other one, the implantation of an adjunct cogeneration plant, fuelled solely by sugarcane trash, was suggested. Among the studied solutions, in addition to confirming the sugarcane trash's high potential as an increment for the extra electricity production, it was possible to obtain, in some cases, an inferior electricity cost compared to the one verified in the previous operational plant. However, by means of the economic analysis, it was ascertained that the current electricity price policy applied to the Brazilian electric market, with frequently lower prices compared to the ones needed to guarantee the return of the investments on the installed capacity expansion, lack of tax incentive and subsidy to the sector are still impediments for the viability of new projects